2019
DOI: 10.1002/cite.201900068
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Methodology for the Investigation of Mercury Adsorption on Activated Carbons

Abstract: In mercury adsorption on activated carbons both physisorptive and chemisorptive mechanisms play a role. The systematic investigation of Hg0 chemisorption is difficult because equilibrium capacities cannot be determined due to slow adsorption mechanisms. Therefore, the present publication suggests a three‐step approach: 1) Breakthrough curves are used to assess the dynamics of Hg0 adsorption. 2) The contributions of physisorption and chemisorption can be distinguished by coupled adsorption and desorption experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In previous publications, 31,32 we have extensively reviewed the literature on physisorptive and chemisorptive singlecomponent adsorption of Hg 0 . Mercury can react chemisorptively with surface groups of activated carbons in the presence of other components such as water, oxygen, sulfur, or chlorine.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications, 31,32 we have extensively reviewed the literature on physisorptive and chemisorptive singlecomponent adsorption of Hg 0 . Mercury can react chemisorptively with surface groups of activated carbons in the presence of other components such as water, oxygen, sulfur, or chlorine.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier publication, we have shown that these activated carbons have predominantly physisorptive sites for the adsorption of Hg 0 . 28 …”
Section: Methodsmentioning
confidence: 99%
“… Flow diagram of fixed bed test unit; a = water bath; b = evaporator; c = cooler; d = tempered reactors 1 and 2; MFC = mass flow controller; AAS = atomic absorption spectrometer according to refs ( 28 ) and ( 29 ). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations